Women, pharmacy and the World Wide Web: could they be the answer to the obesity epidemic?. (31st January 2013) - Fakih, Souhiela; Hussainy, Safeera; Marriott, Jennifer
Abstract Objectives The objective of this article is to explore how giving women access to evidence‐based information in weight management through pharmacies, and by utilising the World Wide Web, is a much needed step towards dealing with the obesity crisis. Key findings Women's needs should be considered when developing evidence‐based information on weight. Excess weight places them at high risk of diabetes and cardiovascular disease, infertility and complications following pregnancy and giving birth. Women are also an important population group because they influence decision‐making around meal choices for their families and are the biggest consumers of weight‐loss products, many of which can be purchased in pharmacies. Pharmacies are readily accessible primary healthcare locations and given the pharmacist's expertise in being able to recognise underlying causes of obesity (e.g. medications, certain disease states), pharmacies are an ideal location to provide women with evidence‐based information on all facets of weight management. Considering the exponential rise in the use of the World Wide Web, this information could be delivered as an online educational resource supported by other flexible formats. Conclusions The time has come for the development of an online, evidence‐based educational resource on weight management, which is combined with other flexible formats and targeted at women in general and according to different phases of their lives (pregnancy, post‐partum, menopause). By empowering women with this knowledge it will allow them and their families to take better control of their health and wellbeing, and it may just be the much needed answer to complement already existing resources to help curb the obesity epidemic.